2019
DOI: 10.1177/0899764019843340
|View full text |Cite
|
Sign up to set email alerts
|

Giving Intention Versus Giving Behavior: How Differently Do Satisfaction, Trust, and Commitment Relate to Them?

Abstract: This research quantifies for the first time in the literature how strong the direct and indirect relationships are between satisfaction, trust, and commitment and giving intention versus giving behavior. We constructed a unique data set of over 17,000 donors from five large charities. We applied the latest mediation framework for categorical variables from consumer behavior. We found that at a group level, most of the direct and indirect effects that exist between satisfaction, trust, commitment, and giving in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…In reality, donor retention is all about focusing on existing donors and finding creative solutions and engaging ways to turn them into repeated and loyal donors [ 37 , 41 , 55 ]. Since the cost of acquiring a new donor is usually higher than that of retaining an existing one and it is able to reflect donor satisfaction [ 44 ], donor retention has become a very important issue for non-profit organizations.…”
Section: Related Workmentioning
confidence: 99%
“…In reality, donor retention is all about focusing on existing donors and finding creative solutions and engaging ways to turn them into repeated and loyal donors [ 37 , 41 , 55 ]. Since the cost of acquiring a new donor is usually higher than that of retaining an existing one and it is able to reflect donor satisfaction [ 44 ], donor retention has become a very important issue for non-profit organizations.…”
Section: Related Workmentioning
confidence: 99%
“…Relationship commitment model. Lee (2004a, 2004b) propose that the importance of trust is mediated (or explained) by relationship commitment (see also Shang et al, 2019). In other words, it is argued that trust in a particular nonprofit cultivates a sense of commitment-a desire to maintain the relationship with that organization-which in turn promotes giving.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The need for trust is viewed as particularly important in situations characterised by complexity, uncertainty or risk, and where there is lack of knowledge on the part of participants to a relationship (O'Loughlin‐Banks & Raciti, 2014), all fairly typical features of relationships between key charity stakeholders. However, when eventually established, the maintenance of trust requires continual attention, as it has been shown that, once created, it has the potential to fade over time and such loss has a significant impact on behaviour (Palmatier, Jarvis, Bechkoff, & Kardes, 2009; Shang, Sargeant, & Carpenter, 2019).…”
Section: Trust and The Charity Sectormentioning
confidence: 99%